The Effect of Green Products, Green Promotion, and Environmental Knowledge on Purchase Decisions for The Body Shop Products in Samarinda City - Sahariah, Siti; Arsyad, Annisa Wahyuni; Hikmah, Mukhibatul; Nadroh, Ummi (Proceedings International Conference on Education Innovation and Social Science, 2025)
In recent years, awareness of the importance of sustainability has been increasing across various industries, including skincare and beauty. Consumers now not only consider the effectiveness of products but also their impact on the environment. This study aims to analyze the positive and significant influence of green products, green promotion, and environmental knowledge on purchase decisions for The Body Shop products. This study is a quantitative correlational research. The respondents in this study were The Body Shop consumers in Samarinda City. The sample was obtained using non-probability sampling with purposive sampling and employing multiple linear regression analysis techniques, with SPSS Statistics 31 as the analysis tool. The results of the study indicate that green products, green promotion, and environmental knowledge have a positive and significant influence on purchase decisions, thereby validating all hypotheses in this study.